2021
DOI: 10.1016/j.jbc.2021.101154
|View full text |Cite
|
Sign up to set email alerts
|

Novel human cell expression method reveals the role and prevalence of posttranslational modification in nonmuscle tropomyosins

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Construct His-FLAG-actin was obtained using overlap extension PCR to add the sequence encoding for a His-FLAG-TEV affinity/cleavage tag (MAHHHHHH-SG-DYKDDDDK-TS-ENLYFQ) N-terminally to the α-actin cDNA [lacking the first two N-terminal residues that are removed posttranslationally ( 10 )]. The construct was inserted between the SalI and BamHI sites of vector pJCX4 (Addgene ID: 170756) ( 47 , 48 ). A SpeI site was silently inserted into the TEV-encoding sequence, and other actin isoforms (β cytoplasmic and γ smooth) were inserted between the SpeI and BamHI sites.…”
Section: Methodsmentioning
confidence: 99%
“…Construct His-FLAG-actin was obtained using overlap extension PCR to add the sequence encoding for a His-FLAG-TEV affinity/cleavage tag (MAHHHHHH-SG-DYKDDDDK-TS-ENLYFQ) N-terminally to the α-actin cDNA [lacking the first two N-terminal residues that are removed posttranslationally ( 10 )]. The construct was inserted between the SalI and BamHI sites of vector pJCX4 (Addgene ID: 170756) ( 47 , 48 ). A SpeI site was silently inserted into the TEV-encoding sequence, and other actin isoforms (β cytoplasmic and γ smooth) were inserted between the SpeI and BamHI sites.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that different mammalian Tpm isoforms associate with actin filaments with different dynamics, and compete with other actin-binding proteins in an isoform-specific manner in vitro (Gateva et al, 2017). Further, tropomyosins contain post-translational modifications (Carman et al, 2021). In fission yeast, phosphorylation of S125 in Cdc8 was shown to significantly reduce its apparent actin Cdc12 from its roles in contractile ring assembly (Bohnert et al, 2013;Willet et al, 2018), but no studies show direct phosphorylation of For3 (of 35 publications mentioning For3 listed on PubMed.gov).…”
Section: Discussionmentioning
confidence: 99%
“…These Tpms contain an acetylation-mimic Met-Ala-Ser sequence in the N-terminus. Tpms purified from mammalian cells that harbor native post-translational modifications, however, display slightly different affinities on actin filaments (Carman et al, 2021). Thus, also the dynamics of native Tpms on actin filaments may exhibit small differences from the ones produced in E. coli .…”
Section: Discussionmentioning
confidence: 99%